The Influence Of Work Discipline, Work Environment Loyalty And Compensation On The Performance Of Village Apparatus In Semidang Alas Maras District - Putri, Jenni Erokda Jumi; Anggriani, Ida; Nurzam, Nurzam (Social Sciences Journal, 2025)
The aim of this research is to determine the influence of work discipline, work environment loyalty and compensation on the performance of village officials in Semidang Alas Maras District. The type of research used is quantitative. The data analysis methods used are multiple linear regression, determination tests, and hypothesis tests. From the calculations, the results obtained by the multiple linear regression equation are: Y=6.366+0.494X1+0.131X2+0,312X3+0,482X4+2.733. Because the direction of the regression is positive, it can be interpreted that work discipline has a significant effect on performance. This can be proven by showing a significant value of 0.000 < 0.05 because the significant value is smaller than 0.05, so Ha is accepted and Ho is rejected. Loyalty also has a significant effect on performance, this is proven by showing a significant value of 0.000 < 0.05 because the significant value is smaller than 0.05, so Ha is accepted and Ho is rejected. The work environment has a significant effect on performance, this is proven by showing a significant value of 0.000 < 0.05 because the significant value is smaller than 0.05, so Ha is accepted and Ho is rejected. Compensation has a significant effect on performance, this can be proven by showing a significant value of 0.000 < 0.05 because the significant value is smaller than 0.05, then Ha is accepted and Ho is rejected. From the Anova table, a value (Sig) of 0.000 is obtained. The significant value is 0.000 < 0.05, which means that if the significant probability value is < 5% (0.05) then all independent variables, Work Discipline (X1), Loyalty (X2), Work Environment (X3), Compensation (X4) have an effect significant to the related variable, Performance Satisfaction (Y) of Village Officials in Semidang Alas Maras District.